Investigation of multiple populations highlight VEGFA polymorphisms to modulate anterior cruciate ligament injury. Issue 7 (18th October 2021) - Feldmann, Daneil C.; Rahim, Masouda; Suijkerbuijk, Mathijs A. M.; Laguette, Mary‐Jessica N.; Cieszczyk, Paweł; Ficek, Krzysztof; Huminska‐Lisowska, Kinga; Häger, Charlotte K.; Stattin, Evalena; Nilsson, Kjell G.; Alvarez‐Rumero, Javier; Eynon, Nir; et al.
Abstract: Polymorphisms in VEGFA and KDR encoding proteins have been associated with anterior cruciate ligament (ACL) injury risk. We leveraged a collective sample from Sweden, Poland, and Australia to investigate the association of functional polymorphisms in VEGFA and KDR with susceptibility to ACL injury risk. Using a case–control genetic association approach, polymorphisms in VEGFA and KDR were genotyped and haplotypes inferred from 765 controls, and 912 cases clinically diagnosed with ACL rupture. For VEGFA, there was a significant overrepresentation of the rs2010963 CC genotype ( p  = 0.0001, false discovery rate [FDR]: p  = 0.001, odds ratio [OR]: 2.16, 95% confidence interval [CI]: 1.47–3.19) in the combined ACL group (18%) compared to the combined control group (11%). The VEGFA (rs699947 C/A, rs1570360 G/A, rs2010963 G/C) A‐A‐G haplotype was significantly ( p  = 0.010, OR: 0.85, 95% CI: 0.69–1.05) underrepresented in the combined ACL group (23%) compared to the combined control group (28%). In addition, the A‐G‐G construct was significantly ( p  = 0.036, OR: 0.81, 95% CI: 0.64–1.02) underrepresented in the combined ACL group (12%) compared to the combined CON group (16%). Our findings support the association of the VEGFA rs2010963 CC genotype with increased risk and (ii) the VEGFA A‐A‐G haplotype with a reduced risk, and are in alignment with the a priori hypothesis. Collectively identifying a genetic interval within VEGFA to be implicated in ACL risk modulation and highlight further the importance of vascular regulation in ligament biology.